Fort George, looking out towards Port-of-Spain and Caroni Plains, Trinidad, W.I. - (:unkn) unknown (Syncreators Ltd., 2010)
Photo of a part of Fort George overlooking Port-of-Spain and Caroni Plains in Trinidad. Also visible is the ordnance used by the British during their military operations. Postcard numbered 6913.
Colour: Blue, Red and Green Hues; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fortification--Trinidad and Tobago; Plains--Trinidad and Tobago; Ordnance--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Historic sites--Trinidad and Tobago; Caroni (Trinidad and Tobago : County); Fort George (Port of Spain)